Transient Expression of Candidatus Liberibacter Asiaticus Effector Induces Cell Death in Nicotiana benthamiana - Pitino, Marco; Armstrong, Cheryl M.; Cano, Liliana M.; Duan, Yongping (Frontiers in Plant Science, 2016)
Candidatus Liberibacter asiaticus “Las” is a phloem-limited bacterial plant pathogen, and the most prevalent species of Liberibacter associated with citrus huanglongbing (HLB), a devastating disease of citrus worldwide. Although the complete sequence of the Las genome provides the basis for studying functional genomics of Las and molecular mechanisms of Las-plant interactions, the functional characterization of Las effectors remains a slow process since remains to be cultured. Like other plant pathogens, Las may deliver effector proteins into host cells and modulate a variety of host cellular functions for their infection progression. In this study, we identified 16 putative Las effectors via bioinformatics, and transiently expressed them in Nicotiana benthamiana. Diverse subcellular localization with different shapes and aggregation patterns of the effector candidates were revealed by UV- microscopy after transient expression in leaf tissue. Intriguingly, one of the 16 candidates, Las5315mp (mature protein), was localized in the chloroplast and induced cell death at 3 days post inoculation (dpi) in N. benthamiana. Moreover, Las5315mp induced strong callose deposition in plant cells. This study provides new insights into the localizations and potential roles of these Las effectors in planta.